Providing a Model for the Enhancement of Accounting Education in Higher Education in Iran - Hosein Naseri; Gholamreza Karami; Rezvan Hejazi (بررسی‌های حسابداری و حسابرسی, 2023)
Objective: This study aims to introduce a framework that enhances the quality of accounting education within the nation's higher education institutions. To clarify, the researcher intends to uncover the key factors influencing the advancement of accounting education within the higher education system by conducting interviews with experts. Methods: The present research is exploratory and descriptive. In this study, a qualitative approach was employed, utilizing the method of thematic analysis to analyze interviews with experts, leading to the identification of pertinent themes. This article employs Atride and Stirling's model to examine themes in three overarching phases. The initial phase involves text analysis, followed by text discovery in the second phase, and culminating in the integration of these discoveries during the third phase. At each of these stages, a higher level of abstraction is essential for a thorough analysis, as per the prescribed steps. This comprehensive three-step process in the theme network model is carried out in six steps. The steps of thematic analysis in the present research based on the Atride and String model include: 1) The first stage of text analysis, in which the coding framework is developed, based on the concepts, theories, and research questions, and the text is broken down into text sections using the framework; 2) Coding done, the second stage of determining and identifying the themes, in which the themes are determined and identified, the themes are abstracted from the coded text sections; 3) The text refined, the third stage of creating a network of themes takes place in the form of a general pattern. Through the expert interviews, the researcher identified research participants using a deliberate and available snowball sampling technique. This method ultimately resulted in the selection of 10 accounting professors, chosen based on their educational backgrounds, fields of expertise, and experience. Results: During the theme identification stage, 130 concepts were initially formulated. After two rounds of input and refinement from experts and supervisors, these concepts were distilled down to 65 core concepts. In the next stage, the organizers focus on the following aspects: the creation of new accounting education arrangements; development of new accounting education tools; alignment of accounting education with contemporary standards; fostering communication between the industry and universities in accounting education; crafting management plans for accounting; enhancing accounting skills; adapting education to accounting-related developments; identifying accounting standards; evaluating the quality and quantity of professors; tailoring educational content to specific areas of expertise; understanding market demands; projecting expected outcomes; facilitating entry into the job market; and promoting entrepreneurial accounting. The semantic and conceptual relationships among these themes were also modeled. Conclusion: To enhance educational conditions, it is imperative to prioritize the improvement of accounting education arrangements and programs, elevate teaching quality and accounting education standards, and enhance the educational and research content in the field of accounting